2020
DOI: 10.1111/jphp.13338
|View full text |Cite
|
Sign up to set email alerts
|

Black mulberry fruit extract alleviates streptozotocin-induced diabetic nephropathy in rats: targeting TNF-α inflammatory pathway

Abstract: Objectives This study was designed to investigate the effect of Morus nigra fruit extract in retarding the progression of diabetic nephropathy in streptozotocin (STZ)-induced diabetic rats. Methods Diabetic male Wistar rats were injected with black mulberry fruit extract (BMFE) at doses of 150 and 300 mg/kg body weight. After 4 weeks, microalbuminuria was estimated in addition to serum concentrations of glucose, insulin, creatinine and albumin. Key findings The study revealed a significant amelioration of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Untreated DM can lead to numerous diseases and long-term complications, leading to death (Lotfy et al 2017). Recent evidence confirms that DM-induced chronic hyperglycemia can induce the formation of oxidative stress and free radicals in humans and animal models (Sadek et al 2017;Abouzed et al 2018;Alsenosy Abdel-wahab et al 2019;Abouzed et al 2020). Oxidative stress is the main factor that induces the secondary complications of DM, such as injuries and foot ulceration (Sivitz and Yorek 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Untreated DM can lead to numerous diseases and long-term complications, leading to death (Lotfy et al 2017). Recent evidence confirms that DM-induced chronic hyperglycemia can induce the formation of oxidative stress and free radicals in humans and animal models (Sadek et al 2017;Abouzed et al 2018;Alsenosy Abdel-wahab et al 2019;Abouzed et al 2020). Oxidative stress is the main factor that induces the secondary complications of DM, such as injuries and foot ulceration (Sivitz and Yorek 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The administration of antioxidants fucoidan nanoparticles can improve kidney function by preventing oxidative tissue damage in diabetic nephropathy. The same result, the administration of exogenous antioxidants such as Syzygium aromaticum , Black mulberry fruit, and Heteroxenia ghardaqensis can inhibit ROS formation by scavenging the intracellular ROS that has been formed [ 17 , 18 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that streptozotocin can cause oxidative stress and inflammation, which can further damage the kidneys in diabetic rat model complications and eventually lead to nephropathy. Thus, agents that have antioxidant and anti-inflammation effects can be used to prevent nephropathy in diabetes [ 18 , 19 ]. It has been reported that fucoidan is a natural product that has a strong antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Diabetic rats treated with mulberry fruit and leaves extract and mix showed an improvement in serum glucose, urea and creatinine levels. Similarly, Abouzed et al, [20] stated that the black mulberry fruit extract ameliorated the renal function biomarkers in diabetic rats. Mulberry extract might advantageously affect diabetic confusions, like renal dysfunction, by keeping up with blood glucose homeostasis in diabetic rats.…”
Section: Discussionmentioning
confidence: 93%
“…Group III (DAPA): diabetic rats received dapagli ozin (1 mg/Kg daily) by gavage as described by Oraby et al, [19] for four weeks following the rst two weeks of diabetes induction. Group IV (MFE): diabetic rats treated with mulberry fruit extract (300mg/kg b.wt) by gavage as described by Abouzed et al, [20] for six weeks. Group V (MLE): diabetic rats treated with mulberry leaves extract (250 mg/kg b.wt) by gavage as Hassanalilou et al, [15] for six weeks.…”
Section: Experimentation Protocolmentioning
confidence: 99%